Development of architectural environment of underground structures of public and trading complexes on the example of reconstruction of Paveletsky station square - E. V. Mikhaylova; E. K. Kalinichenko; M. O. Belova (Vestnik MGSU)
Introduction. The relevance of studying the development of underground multi-level structures of public and trade complexes (PTC) is determined by the need for active development of underground space in large and major cities in accordance with the Strategy of Spatial Development of Russia until 2025. The formation of immersive environment in the complexes based on VR/AR technologies was facilitated by socio-economic conditions associated with the implementation of the federal project “Digital Technologies” until 2024. Active integration of landscape elements into the structure of the centres is caused by the need for environmental rehabilitation of urban areas in accordance with the Environmental Safety Strategy of the Russian Federation until 2025. The aim of the research is to identify the peculiarities of the development in the 2020s of the architectural environment of multi-level underground structures of public and trade complexes in the context of reconstruction of the central districts of large and major cities in areas that include a large urban square, using the example of the “Paveletskaya Plaza” underground multifunctional centre. The task of the analysis is to determine new trends in the development of the architectural environment of the PTC in the modern socio-economic, urban planning, environmental conditions of large and major cities that meet their requirements.Materials and methods. The study of literary sources, scientific publications, Internet resources, as well as field surveys of the complexes. Development of schematic spatial models of the complexes based on the identified modern trends of their architectural and planning organization.Results. The necessity to refine the existing PTC classification in the sites that include a large urban area has been identified.Conclusions. The omnichannel behavior of buyers requires development of architectural environment of the centres based on the expansion of volume and composition of public function, development of techniques of immersive environment creation, as well as the formation of a landscape at above-platform levels.